The influence of leadership style, work discipline, job satisfaction, and work environment on employee performance BKKBN Kota Palopo - Indra Kusdarianto; Ramlawati Ramlawati; Masdar Mas’ud (Institute of Computer Science (IOCS), 2023)
Performance is the result of work in quality and quantity achieved by employees in carrying out their duties in accordance with the responsibilities given to them. Many factors cause human resources to have superior performance so as to encourage organizational performance. These factors such as leadership style have a strong influence on the running of the organization and the survival of the organization. Furthermore, other factors that can affect performance are work discipline, job satisfaction, and work environment. This study aims to determine the effect of leadership style, work discipline, job satisfaction and work environment on the performance of employees of the Badan Kependudukan dan Keluarga Berencana Nasional (BKKBN) of Palopo City, South Sulawesi. The population in this study were all employees of the BKKBN of Palopo City, South Sulawesi as many as 143 people. However, the sample used was 105 people with the Slovin Formula. Sampling using simple random sampling. The analysis method used is descriptive analysis and multiple linear regression analysis. The results showed that leadership style and work discipline affect the performance of employees of the BKKBN of Palopo City, South Sulawesi, while job satisfaction has no effect on the performance of employees of the BKKBN of Palopo City, South Sulawesi. And the work environment affects the performance of employees of the BKKBN of Palopo City, South Sulawesi. Then leadership style, work discipline, job satisfaction and work environment simultaneously affect the performance of employees of the BKKBN of Palopo City, South Sulawesi.